The Role of Skeptical Evidence in the First and Second “Meditations”. Article 2. Certitudo - Khoma, Oleg (Sententiae, 2017)
The author argues that according to Sextus Empiricus, (a) the "sensual" nature of the phenomenon is a metaphorical notion, since it is indistinguishably extended both to sensuality and thinking; (b) the phenomenon manifest itself with irresistible force of impact, through a wide range of passive states of mind; (c) the impact of phenomena is always mediated by our ego, because all skeptic expressions are strongly correlated with the first person singular. The article proves that Descartes could not refute the “excess” of skeptical doubt and make an immanent critique of skepticism without borrowing the aforementioned statements of Sextus. Such borrowing (1) has created a common ground for discussion between Descartes and skeptics; (2) made it possible for the meditator to give persuasiveness to careful observation of his own internal experience. Descartes’ search for certainty in "Meditations" is entirely based on [а] evidence of "phenomena", "states of mind", "passions"; [b] refusal to agree with the "non-evident" proclaimed by Sextus Empiricus.